Analisis Laporan Keuangan Untuk Memprediksi Tingkat Kebangkrutan Dengan Menggunakan Metode Altman Z-Score Modifikasi Pada PT Akasha Wira International Tbk, PT Campina Ice Cream Industry Tbk, PT Sariguna Primatirta Tbk, PT Mayora Indah Tbk, PT Indofood Suk - Kristina, Dina; Nawawi, Achmad (Peneliti.net, 2024)
The purpose of this study was to determine financial performance and bankruptcy potential using the Modified Altman Z-Score method in the companies studied. The data analysis technique in this study is Quantitative Descriptive. The annual financial reports of the companies studied as secondary data. The results of this study show that [1] The financial performance of the companies PT Campina Ice Cream Industry Tbk and PT Mayora Indah Tbk, 2017-2022 shows that X1 is capable of paying short-term obligations, X2 and X3 are able to make a profit or make a profit, X4 is able to fulfill its long-term obligations. PT Akasha Wira International Tbk, PT Sariguna Primatirta Tbk, and PT Indofood Sukses Makmur Tbk have smaller assets compared to their current liabilities, X2 and X3 are able to generate profits or seek profits, X4 is able to fulfill its long-term obligations. [2] The potential for bankruptcy in the companies studied using the Modified Altman Z-Score method. Based on the above research results, it can be concluded that there is no potential for bankruptcy. Because overall each company shows results that are quite healthy and safe. with an average z-score > 2.6.